Perioperative do-not-resuscitate orders: Trainee experiential learning in preserving patient autonomy and knowledge of professional guidelines. Issue 11 (19th March 2021) - Kushelev, Michael; Meyers, Lori D; Palettas, Marilly; Lawrence, Alec; Weaver, Tristan E.; Coffman, John C.; Moran, Kenneth R.; Lipps, Jonathan A.
Abstract : Abstract: Anesthesiologists and surgeons have demonstrated a lack of familiarity with professional guidelines when providing care for surgical patients with a do-not-resuscitate (DNR) order. This substantially infringes on patient's self-autonomy; therefore, leading to substandard care particularly for palliative surgical procedures. The interventional nature of surgical procedures may create a different mentality of surgical "buy-in, " that may unintentionally prioritize survivability over maintaining patient self-autonomy. While previous literature has demonstrated gains in communication skills with simulation training, no specific educational curriculum has been proposed to specifically address perioperative code status discussions. We designed a simulated standardized patient actor (SPA) encounter at the beginning of post-graduate year (PGY) 2, corresponding to the initiation of anesthesiology specific training, allowing residents to focus on the perioperative discussion in relation to the SPA's DNR order. Forty four anesthesiology residents volunteered to participate in the study. PGY-2 group (n = 17) completed an immediate post-intervention assessment, while PGY-3 group (n = 13) completed the assessment approximately 1 year after the educational initiative to ascertain retention. PGY-4 residents (n = 14) did not undergo any specific educational intervention on the topic, but were given the same assessment. The assessment consisted of an anonymized survey that examined familiarity with professional guidelines and hospital policies in relation to perioperative DNR orders. Subsequently, survey responses were compared between classes. Study participants that had not participated in the educational intervention reported a lack of prior formalized instruction on caring for intraoperative DNR patients. Second and third year residents outperformed senior residents in being aware of the professional guidelines that detail perioperative code status decision-making (47%, 62% vs 21%, P  = .004). PGY-3 residents outperformed PGY-4 residents in correctly identifying a commonly held misconception that institutional policies allow for automatic perioperative DNR suspensions (85% vs 43%; P  = .02). Residents from the PGY-3 class, who were 1 year removed the educational intervention while gaining 1 additional year of clinical anesthesiology training, consistently outperformed more senior residents who never received the intervention. Our training model for code-status training with anesthesiology residents showed significant gains. The best results were achieved when combining clinical experience with focused educational training.